(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article offered to attention attempts to isolate and describe the linguacultural component of modern bilingualism, to give a theoretical generalization to the analysis of the studied information. Sociolinguistic interpretation of bilingualism allows us to look at the associative indicators of this linguacultural phenomenon in a slightly different way.